International priorities for home care education, research, practice, and management: Qualitative content analysis. (February 2019) - Jarrín, Olga F.; Pouladi, Fatemah Ali; Madigan, Elizabeth A.
Abstract: Background: Despite growing demand for home care nursing, there is a growing home care workforce shortage, due in part to hospital-centric nursing curricula that lead students to undervalue of home care and community practice setting (Van Iersel et al., 2018a, 2018b). Objectives: Articulate an international vision for the future of home care education, research, practice, and management shared by experienced home care nurses working in leadership roles. Design: Qualitative content analysis. Settings and Participants: The sample included 50 home care professionals from 17 countries. Methods: Home care nurse leaders (in education, research, practice, and management roles) were recruited through professional international nursing networks to participate in a structured online survey about priorities for the future of home care in 2014. Responses were open coded by two independent researchers. Preliminary categories and sub-themes were developed by the research team and revised after a modified member-checking process that included presentation and discussion of preliminary findings at three international nursing meetings in 2015 and 2016. Results: Four major themes emerged reflecting international priorities for the future of home care education, research, practice, and management: 1) Build the evidence base for home care; 2) Design better systems of care; 3) Develop leaders at all levels; and 4) Address payment and policy issues. Conclusions: Collectively, the findings provide a major call to action for nurse educators to re-design existing pre- and post-licensure educational programs to meet the growing demand for home care nurses. Innovations in education that focus on filling gaps in the evidence-base for community nursing practice, and improving access to continuing education and evidence-based resources for practicing home care nurses and nurse managers should be prioritized. Highlights: Global priorities for the future of home care education, research, practice, and management include: A call to generate (and use) evidence-based guidelines for home care A call to re-design health systems for home care A call to develop home care leaders at all levels A call to address payment and policy issues that create barriers to care